Manitoba Grade 9 Students' Satisfaction with Life - Thomas Falkenberg; Rebeca Heringer; Bhanu Pilli (Brock University, 2024)
Over the last fifteen years, student well-being has become of greater concern in school education in Canada and beyond. However, there is very little data available on how well Canadian students are. The study that will be reported on in this paper provides such data, specifically the province of Manitoba. Using the Satisfaction with Life Scale, the study collected data from 1587 grade 9 students on their self-assessed satisfaction with how their lives are going. The data were collected with two demographic variables: regional location of the schools the participating students attended (norther, rural, urban) and their self-declared gender. While in the study the majority of participating students were satisfied with how their lives were going, a concerning number of students were dissatisfied or extremely dissatisfied with their lives. Furthermore, the data suggest a statistically significant difference in life satisfaction between girls (lower) and boys (higher). The study did not find a statistically significant difference between life satisfaction across the three types of regional location.